عباس آرام کے نام اقبال کے خطوط (جشن فردوسی کے موقع پر ٹیگور کے دورہ ایران اور زرتشتی مذہب کے احیاء پر تبصرہ): Iqbal’s Letters to Abbas Aram (Comment on Tagore’s visit to Iran and the revival of Zoroastrianism on the occasion of Ferdowsi Festival.) - حسین ڈاکٹر یوسف (Tashkeel e Jadeed, 2024)
The following article summarizes and explains the theme of four letters of Allama Iqbal which he wrote in 1932 to Abbas Aram, an Iranian diplomat. In these successive letters, three basic and important things have been mentioned. The purpose of the letters was to keep Iranians informed of the modern realities and conspiracies that the colonial powers had started through their propaganda in that time. The letters cover Allama's views on the future of Muslims in West Asia, commentary on some literary topics and books, motives and goals of Tagore’s visit to Iran, and the rumor of conversion of Iranian state religion to Zoroastrianism during the Shah's reign. Another letter addressed to Iqbal was sent to G.K. Nariman, a Parsi journalist in Bombay, in which he has informed Allama of the real facts behind the ongoing conspiracies. Allama has sent the details of this letter to Abbas Aram. The text of the letters is in English. This article sheds light on the background and reasons for writing all these letters.